Changes in awareness and utilization of social participation mechanisms of the Colombian Health Care System in the last 10 years - Delgado-Gallego, María Eugenia; Vázquez Navarrete, Maria Luisa (International journal of health services, 2012)
This article seeks to analyze changes in awareness and utilization of social participation mechanisms of the Colombian health care system in the last 10 years by comparing two cross-sectional studies based on surveys among health care users in 2000 and 2010. The results show that while in 2000, the level of awareness and utilization of the mechanisms were low, in 2010 researchers identified a significant tendency toward further diminishing of awareness and utilization. In both surveys, the best-known and most-used participation mechanisms were the market mechanisms. Also in both surveys, individuals from the rural zone were aware of and used the mechanisms. In the first survey, men were more aware of the mechanisms and used them more frequently, but it was women in the second survey who presented higher rates of awareness and use; these differences, however, were not statistically significant. The results herein indicate that effective social participation in the General Social Security System in Health is far from being achieved. The policy has failed to materialize, as evidenced by the lack of balance in the participation of one of the main actors of the General Social Security System in Health: the users.
Gesehen am 26.11.2018